Outcomes of simultaneous pancreas and kidney transplants based on preemptive transplant compared to those who were on dialysis before transplant – a retrospective study. (18th June 2020) - Parajuli, Sandesh; Swanson, Kurtis J.; Patel, Ravi; Astor, Brad C.; Aziz, Fahad; Garg, Neetika; Mohamed, Maha; Al‐Qaoud, Talal; Redfield, Robert; Djamali, Arjang; Kaufman, Dixon; Odorico, Jon; et al.
Summary: Among kidney transplant recipients, the duration of pretransplant dialysis is significantly associated with worse post‐transplant outcomes. However, data on the outcomes of preemptive simultaneous pancreas and kidney (SPK) are limited. We analyzed primary SPK recipients transplanted between January 2000 and December 2017. Patients were divided into two groups based on pretransplant dialysis history of preemptive versus non‐preemptive. Patient and survival of grafts were outcomes of interest. Of the 644 recipients, 174 (27%) were preemptive and 470 (73%) were not. Most of the baseline characteristics were similar between the groups. In the univariable analysis, the non‐preemptive transplant was associated with 54% increased risk for kidney death‐censored graft failure (DCGF; HR: 1.54; 95% CI: 1.01–2.35; P = 0.05). There was a 29% increased risk after adjustment for confounding factors (HR: 1.29; 95% CI: 0.83–2.02; P = 0.26), although this association was not statistically significant. Similarly, there was a 16% increased risk of pancreas DCGF in univariable analysis and 1% after adjustment, which was also not statistically significant. When outcomes were based on the duration of pretransplant dialysis, the duration was not associated with either patient survival or survival of either graft in K‐M analysis. In SPK recipients, with pretransplant dialysis history, there was a tendency toward inferior graft survival, mainly for the kidney more than the pancreas.